The efficacy of olaparib as salvage therapy in an advanced intrahepatic cholangiocarcinoma patient harboring somatic BRCA1 and PALB2 pathogenic variants: a case report and literature review - Wang, Jian; Zheng, Qinhong; Chen, Jianxin (Frontiers in Pharmacology, 2025)
BackgroundFor advanced biliary tract cancer (BTC) patients with BRCA pathogenic variants who have failed first-line treatment, the optimal treatment strategy remains to be established. Olaparib, the first FDA-approved poly adenosine diphosphate-ribose polymerase inhibitors (PARPi), is commonly utilized in clinical practice for breast, ovarian, prostate, and pancreatic cancers that harbor germline or somatic BRCA pathogenic variants through a mechanism known as “synthetic lethality”. However, the proportion of BTC patients with BRCA pathogenic variants is relatively low, estimated at approximately 1%–7% of all BTC cases, leading to inconclusive evidence regarding the efficacy of targeted therapy with PARPi for these patients.Case presentationWe presented a case of a patient with advanced intrahepatic cholangiocarcinoma (iCCA) harboring dual somatic homologous recombination repair (HRR) gene pathogenic variants, specifically BRCA1 and PALB2, who achieved PR lasting approximately 7 months following salvage treatment with olaparib.ConclusionWe considered that the BTC population with dual HRR pathogenic variants, which include a BRCA pathogenic variant, might represent an advantageous cohort for olaparib treatment. Furthermore, in addition to BRCA pathogenic variant, PALB2 pathogenic variant may potentially serve as the next clinical predictive target for PARP inhibitors in the BTC population. A systematic summary and analysis of existing studies on BTC patients with pathogenic variants indicate that these patients might derive benefits from olaparib; however, further validation in a larger cohort is necessary.